Social vulnerability in the adaptation of rural communities to climate change in Imo State, Nigeria - Okoro, Franklin Chimaobi (University of the Witwatersrand, Johannesburg, 2024)
Rural communities in developing countries such as Nigeria are faced with frequent extreme weather/climate events that impact their economy, health, and environment due to the combination of high social vulnerabilities, low social resilience, and low adaptive capacities. The aim of this study is to investigate the root causes of social vulnerability in rural communities in Nigeria and how rural households use their social capital and networks to adapt to the impacts of climate change. The study used ten (10) social vulnerability indicators (factors) to ascertain their influence on social resilience and adaptive capacity during climate related disasters. To achieve this purpose, three communities in Imo State, Southern Nigeria were selected, and distributed 240 structured questionnaires to rural household heads, interviewed 18 local stakeholders and climate change actors (government agencies), and conducted three (3) Focus Group Discussions (FGDs) with group of farmers from the three selected communities. The questionnaire survey, interview, and FGD guides contained open-ended questions that allowed participants to report freely. The quantitative data derived from the questionnaire survey were subjected to descriptive analysis using SPSS while the qualitative data were subjected to thematic analysis to derive relevant themes for discussions. The result of the study shows that social vulnerability is a function of age, gender, education, household size, income, sources of livelihood, disability, means of transport, access to healthcare, and alternative accommodation being available during climate emergencies. The study further shows that social vulnerability of rural residents was exacerbated by societal vulnerability influenced by political, economic, cultural, and social factors. Although there are other weather/climate extreme events (disasters), however, the most prominent is floods, constituting 48.3% of the weather/climate events experienced in the study area with its impacts requiring more efficient climate adaptation strategies other than the traditional measures like relocation/migration, use of early maturing crop varieties, early planting and harvesting. However, rural households drew support from government, NGOs, and oil companies but the help from family members, friends, neighbours, social group members (social networks) were more beneficial and helped more rural residents to improve their social resilience. The study recommends that rural residents be encouraged to join social groups since their memberships in such groups will help to improve their social resilience, and that government and its agencies should engage multi-stakeholders in their genuine efforts to develop more effective measures for climate change adaptation.
A research report submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Geography and Environmental studies, School of Geography and Environmental studies University of the Witwatersrand, Johannesburg, 2024
Keywords: SOCIAL VULNERABILITY; RURAL COMMUNITIES; CLIMATE CHANGE; ADAPTATION; RESILIENCE; SOCIAL CAPITAL; SOCIAL NETWORK; DISASTER RISK REDUCTION; UCTD; SDG-13: Climate action